Dealing with the unknown: perceptions, fears and worries of SARS-CoV-2 infection among hospital workers - Mireia Utzet; Rocío Villar; Pilar Díaz; Maria Dolors Rodríguez Arjona; José María Ramada; Consol Serra; Fernando G. Benavides (Elsevier, 2023)
Objective: This study explores fears and worries regarding SARS-CoV-2 risk of infection and transmission to relatives, co-workers, and patients in relation to non-pharmacological preventive interventions among healthcare workers (including physicians, nurses, aides, cleaners, maintenance, and security staff) in a healthcare institution in Barcelona (Spain), during the first and second waves of the SARS-CoV-2 pandemic. Method: The research used an explorative qualitative approach. Six focus groups and ten individual interviews were conducted online and audio-recorded, transcribed verbatim and analysed using thematic analysis and mixed coding. Results: Forty professionals participated in the study. Four common themes emerged in all groups: challenges related to the lack of pandemic preparedness, concerns about personal protective equipment, unclear guidelines for case and contact tracing, and communication-related difficulties. Conclusions: This study emphasizes the key recommendations to improve non-pharmacological preventive interventions to reduce workers' fears and worries about the risk of infection and spreading the infection to others, including families. Above all, these should include ensuring the availability, and correct use of adequate personal protective equipment, improve guidelines on case and contact tracing, and setting effective communication channels for all workers of the organization. These recommendations must be reinforced in maintenance and security personnel, as well as night shift nurses and aides, to also reduce health inequalities. Resumen: Objetivo: Este estudio explora los temores y las preocupaciones respecto al riesgo de infección y transmisión del SARS-CoV-2 a familiares, compañeros de trabajo y pacientes en relación con las intervenciones preventivas no farmacológicas entre el personal hospitalario (incluido personal de medicina, personal de enfermería y auxiliares, y personal de limpieza, mantenimiento y seguridad) de una institución sanitaria de Barcelona (España), durante la primera y segunda oleadas de la pandemia por SARS-CoV-2. Método: La investigación utilizó un enfoque cualitativo exploratorio. Se realizaron seis grupos focales y diez entrevistas individuales en línea, que se grabaron en audio, se transcribieron literalmente y se analizaron mediante análisis temático y codificación mixta. Resultados: Participaron en el estudio 40 profesionales. En todos los grupos surgieron cuatro temas comunes: retos relacionados con la falta de preparación ante una pandemia, preocupaciones sobre el equipo de protección personal, directrices poco claras para el rastreo de casos y contactos, y dificultades relacionadas con la comunicación. Conclusiones: Este estudio hace hincapié en las recomendaciones clave para mejorar las intervenciones preventivas no farmacológicas con el fin de reducir los temores y las preocupaciones de los trabajadores sobre el riesgo de infección y de contagio a otras personas, incluidas las familias. Por encima de todo, estas deben incluir garantizar la disponibilidad y el uso correcto de equipos de protección individual adecuados, mejorar las directrices sobre el rastreo de casos y contactos, y establecer canales de comunicación eficaces para todos los trabajadores de la organización. Estas recomendaciones deben reforzarse en el personal de mantenimiento y seguridad, así como en el personal de enfermería y auxiliares del turno de noche, para reducir también las desigualdades sanitarias.